Undetected for a century: Palaearctic Agrilus ribesi Schaefer (Coleoptera: Buprestidae) on currant in North America, with adult morphology, larval biology and DNA barcode - Jendek, Eduard; Grebennikov, Vasily V.; Bocak, Ladislav (Zootaxa, 2015)
We report the Eurasian species Agrilus ribesi Schaefer, 1946, for the first time from North America and propose that the damage to currants (Ribes spp.) in Ontario prior to 1940 and ascribed to A. cuprescens were caused by this species. We provide morphological diagnostic characters for A. ribesi and closely related A. cuprescens and we complement this information with DNA barcodes from four alien Agrilus species established in North America (i.e., A. ribesi Schaefer, A. cuprescens (Ménétriés), A. planipennis Fairmaire and A. sulcicollis Lacordaire) to enable DNA-based identification of these invasive species. Additionally, published information on A. ribesi is summarized and new data are provided on the host plants and biology of larva in North America. The distribution of A. ribesi is mapped, both in its native Palaearctic region and in Canada and the USA, together with the range of its potential host plants in North America. A. ribesi was recovered as a sister-species of A. cuprescens on the neighbor joining DNA barcoding tree and low genetic variability of North American populations may indicate a single introduction to North America for each of these species.